Implementation of Elgamal Elliptic Curve-Based Cryptographic Systems (ECEG) in Text Encryption - Kenanga Dylla Oktariza; Meira Parma Dewi (Mathematical Journal of Modelling and Forecasting, 2025)
Modern cryptography continues to evolve to meet the challenges of information security in the digital age. One of the most widely used algorithms is ElGamal's Elliptic Curve (ECEG). This public-key cryptography-based encryption method offers a high level of security with better computational efficiency than classical algorithms. This study implements the ECEG algorithm in the text encoding process to ensure data confidentiality and integrity. The encryption process is performed using the recipient's public key, while decryption is performed using the corresponding private key. The entire encryption and decryption process in this algorithm can be understood mathematically through operations on elliptical curves. The purpose of this study is to determine the peculiarities of each elliptical curve selected on an ECEG. This study uses a curves y^2=(x^3+8x+25) mod 37 generates all the points on the curve that can be used as a generator that will represent all the letters in the alphabet and numbers from 0 to 9.